2017
DOI: 10.1002/nau.23342
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of the T‐DOC® air‐charged catheters: An alternate technology for urodynamics

Abstract: Aims: Urodynamics (UDS) is widely used for the diagnosis of lower urinary tract dysfunction. Air-Charged catheters (ACC), one of the newer technologies for UDS pressure recording, has been adopted in growing numbers around the world for the past 15 years. Currently, there is a lack of published studies characterizing specific performance of the ACC. Since linearity, hysteresis, pressure drift, and frequency response are important components in characterizing accuracy for cathetermanometer systems; this study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…6b). The air‐charged catheter was chosen to avoid movement artefacts; however, a drift over long‐term measurement has been reported 19 . Additionally, sensing membrane characteristics might become augmented as a result of mucosal contact, and adherent mucus precipitation might play a role.…”
Section: Discussionmentioning
confidence: 99%
“…6b). The air‐charged catheter was chosen to avoid movement artefacts; however, a drift over long‐term measurement has been reported 19 . Additionally, sensing membrane characteristics might become augmented as a result of mucosal contact, and adherent mucus precipitation might play a role.…”
Section: Discussionmentioning
confidence: 99%
“…While no test is without flaws and the ICS standard cystometry is performed with a fluidfilled system, air-charged catheters have gained popularity and have been shown to meet the technical requirements to be used as a pressure-measuring instrument for UDS. 1,18 Additionally, they eliminate the risk of air bubble interference and movement artifacts. 19 Though there is some mixed data regarding the outcomes of anti-incontinence procedures based on VLPP, there have been several studies and a meta-analysis demonstrating the superiority of retropubic tension-free vaginal tape in patients with intrinsic sphincter deficiency (ISD).…”
Section: Discussionmentioning
confidence: 99%
“…Bump et al found that 8F VLPPs were significantly higher than 3F VLPPs. While no test is without flaws and the ICS standard cystometry is performed with a fluid‐filled system, air‐charged catheters have gained popularity and have been shown to meet the technical requirements to be used as a pressure‐measuring instrument for UDS . Additionally, they eliminate the risk of air bubble interference and movement artifacts …”
Section: Discussionmentioning
confidence: 99%
“…It is amazing that AC catheters systems seem to have overtaken the urodynamic market although we do not know the real potential of AC catheters, what the problems are, and how these may be avoided or solved. There are some careful studies comparing AC and WF in models and a reasonable study on patients which show some aspects of agreement and disagreement between AC and WF. This new publication does not contribute anything useful, rather the opposite.…”
Section: Air‐charged Versus Water‐filled or Bad Data Versus Good Urodmentioning
confidence: 99%